(untitled) (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: The aim of this study was to investigate the seroprevalence of coinfections with bovine herpes virus-1 (BHV-1), bovine viral diarrhea (BVD), bluetoungue virus (BTV) and bovine herpes virus-4 (BHV-4) in cattle with reproductive problems in Sudan, and to determine the relation of single or mixed seropositivity with abortion, infertility and death after birth. Materials and methods: Meta-analysis of the results from our earlier serosurveys conducted with a total of 688 dairy cattle was carried out in order to determine prevalence of seropositivity of single and mixed (coinfection) viral infections. Reults: The meta-analysis of the data indicated high seroprevalence of coinfections with various combinations of these agents; only few animals were singly infected. An infection with BHV-1 was observed to be higher than the prevalence of associations between BHV-1 and the other three viral agents. Prevalence of seropositivities to coinfection with BHV-1/BTV; BHV-1/BVD; BHV-1/BTV/BVD were the highest while seropositivities prevalences that involved BHV-4 were much lower. The highest abortion rates were encountered in coinfections with BHV-1/BVD/BTV (31%) and BHV-1/BVD/BTV/BHV-4 (30%) while most infertility cases were noticed in coinfection with BHV-1/BVD/BTV (44%) and BHV-1/BVD/BTV/BHV-4 (21%), and coinfections with the four viruses were encountered in most of the death after birth cases (25%). Overall mixed infections with BHV-1/BVD/BTV (34%) and BHV-1/BVD/BTV/BHV-4 (22.5%) were involved in the majority of reproductive problems studied. Conclusion: Mixed infections constitutes the vast majority of cases and are involved in the majority of reproductive disorders investigated. The high prevalence of seropositivity to all of the four viruses should call for an intervention strategy to reduce the impact of these viruses. http://doi.org/10.5455/javar.2016.c169